PENGARUH E-TRUST, PROMOSI DAN E-SATISFACTION TERHADAP E-LOYALTY PADA P ENGGUNA E-WALLET OVO - Benny Anggara; Chelena gweendolyn; Mohd. Nawi Purba; Ara Auza (Mount Hope Management International Journal, 2024)
OVO is a smart application that provides online payment and transaction services (OVO Cash). This study aims to determine and analyze the effect of E-Trust, Promotion and Promotion on E-Loyalty on OVO E-Wallet Users. This research approach is based on a quantitative approach. The research sample was 80 respondents. Data collection techniques used questionnaires, interviews and documentation. Data analysis techniques used multiple linear regression analysis. The results of the study showed that E-Trust had an effect on E-Loyalty on OVO E-Wallet Users (3.174> 1.992 and 0.002 <0.05), Promotion had an effect on E-Loyalty on OVO E-Wallet Users (3.385> 1.992 and 0.001 <0.05) and E-satisfaction had an effect on E-Loyalty on OVO E-Wallet Users (4.338> 1.992 and 0.000 <0.05). The results of simultaneous hypothesis testing obtained that E-Trust, Promotion and E-Satisfaction had an effect on E-Loyalty for OVO E-Wallet Users (F count (26.977) > F table (2.72) and a significance probability of 0.000 < 0.05).